(untitled) (Archive of Conferences, 2021)
Algorithmic abilities of preschool children are the ability to follow an ideal plan in the process of its implementation, to define in detail the results of algorithmic actions in speech, to present the algorithm, to change and correct algorithmic actions. In the preschool child, in his opinion, it is possible to shape the development of algorithmic thinking in the process of modeling different algorithms in the form of children’s games.